Determinants of business innovation activities in manufacturing industries – Czech Republic and Estonia case study - Prokop, Viktor; Stejskal, Jan (University of Split, 2016)
Economic entities facing an ever accelerating pace of changes, which brings with it advantages and disadvantages. In recent years, the OECD described the Czech Republic and Estonia as a strengthening economies focusing on the promotion of research, development and innovation. However, finding of proper determinants of innovative activities represent a complex process lacking universal formula of which variables positively affect innovation creation. Prior studies showed the number of factors influencing innovation activities. Purpose of this article is to show that the proper combinations of these factors allow creation of more significant effects influencing the growth of companies´ turnover. We created own multiple linear regression models by using data from Community Innovation Survey conducted in the Czech Republic and Estonia between the years 2010-2012 to test the relationship between dependent variable represented by % of turnover in new or improved firms´ products and selected determinants of innovation activities. The aim of this article is to measure direct effects of individual determinants of business innovation activities on growth of turnover in innovated products in the manufacturing industry in the Czech Republic and Estonia and compare them with results of combinations of these factors. We show that both countries are more effective by using proper combinations of selected determinants of innovation activities. Specifically, we show that, by combining cooperation on innovation with different partners, companies in Estonian manufacturing industry are more effective and more significantly affect their growth of turnover than companies in the Czech Republic. We also show that in both countries there is a growing inefficiency in provision of public subsidies (from national or European funds).
Determinanty podnikatelských inovačních aktivit ve zpracovatelském průmyslu - případová studie České republiky a Estonska
Keywords: Determinants; business; innovation; activities; manufacturing; industries; Czech; Republic; and; Estonia; case; study; Determinanty; podnikatelských; inovačních; aktivit; zpracovatelském; průmyslu; případová; studie; České; republiky; Estonska